Physical Health Status of Private Undergraduate Students in Hebei Province: Influencing Factors and Improvement Strategies - Qiao, Lu; Soriano, Dahlia (EDUTREND: Journal of Emerging Issues and Trends in Education, 2026)
This study examines the physical health status of private undergraduate students in Hebei Province by integrating anthropometric indicators with lifestyle behaviors and contextual factors. Using a mixed-methods approach, data were collected from 200 students through physical measurements, structured questionnaires, and semi-structured interviews. The results show that although most students fall within the normal Body Mass Index (BMI) range, significant health risks persist due to insufficient physical activity, irregular exercise frequency, unbalanced dietary habits, and inadequate sleep patterns, particularly among upper-year and female students. Unlike previous studies that primarily rely on physical fitness indicators, this study provides new evidence by revealing a clear disconnect between normal anthropometric outcomes and unhealthy lifestyle behaviors, highlighting that BMI alone is insufficient to represent students’ overall physical health. The findings further indicate that individual behaviors are closely shaped by institutional constraints, academic pressure, family expectations, and socio-cultural norms. The study contributes theoretically by supporting a holistic health framework that integrates social determinants, motivational factors, and institutional support systems. From a policy perspective, the findings underscore the need for coordinated, multi-level health promotion strategies involving curriculum reform, campus-based physical activity initiatives, digital health support, and family engagement to foster sustainable improvements in student well-being.